Unforgiven a Fallen novel - Kate, Lauren (New York Delacorte Press, 2015)
After finding out that Lilith, the mortal he fell in love with centuries ago, is living in constant cycles of Hell, dark angel Cam makes a deal with the Devil and has fifteen days to convince Lilith that he loves her and she loves him
1
Keywords: Angels -- Fiction; High schools -- Fiction; Love -- Fiction; Reincarnation -- Fiction; Schools -- Fiction; Supernatural -- Fiction